A framework for software requirement ambiguity avoidance - Ashok Kumar Gupta Gupta; Aziz Deraman (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This research deals with software requirements ambiguity problems. Among these are incomplete, incorrect, improper, inaccurate and unambiguous requirements. Interestingly, published material related to Software Requirements Specifications (SRS) problems discusses ambiguity as one of the most conversed problems. This paper proposes a Software Requirement Ambiguity Avoidance Framework (SRAAF) to assist and support requirement engineers to write unambiguous requirements, by selecting correct elicitation technique based on the evaluation of various attributes and by applying the W6H technique. We explored existing theories and the outcomes of experimental research to construct the framework. On the basis of existing and inferred knowledge, we tried to justify proposed frameworks components. Our selection process focuses on various situational attributes. We added various situational attributes related to project, stakeholders and requirement engineer for the selection process. Newly devised approach chooses techniques other than traditional techniques or most common techniques and deals with ambiguity to capture the correct requirements information from stakeholders. The framework will be able to address the selection and ambiguity issues in a more effective way and can handle vagueness. New evidence related to attributes and adequacy matrix can be easily added to the framework without any inconvenience.